Gerakan Ekofeminisme Perempuan Muslimah Pesisir dalam Adaptasi Perubahan Iklim di Surabaya Jawa Timur - Ahmad Sihabul Millah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2016)
This article will describe the origins of the ecofeminism movement by costal Muslim women in environmental conservation and the forms of their movement in climate change adaptation in coastal Wonorejo Rungkut Surabaya. To discus these problems, researcher use qualitative research with the case study. The research was conducted in the Village of Wonorejo, distric of Rungkut, Surabaya, East Java. The results showed that the origin of women’s ecofeminism movement were besed on coastal erosion, massive ilegal logging of mangrove and the rising of sea levels. The forms of adaption done by Muslim women in the context of adaptation to climate change were follows. The first doing was the care for the conservation of mangrove forests. The second adapatation was the strengthening of soft skills (Capacity building) in diversification of mangrove plants to be used as batik, syrup and dodol, lerak, and so forth. The third actions, women become economically independent by earning extra income from the diversification of mangroves.